2023
DOI: 10.1093/plphys/kiad027
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin-priming enhances maize seedling drought tolerance by regulating the antioxidant defense system

Abstract: Drought stress (DS) challenges sustainable agriculture production by limiting crop growth and development. The objective of the study was to evaluate the effect of melatonin-priming on enzymatic and non-enzymatic antioxidant defense mechanisms and its relation with leaf ultrastructure and stomatal traits in maize (Zea mays) seedlings under DS (PEG-6000). Drought stress drastically decreased seed germination, plant growth, and leaf chlorophyll content due to excessive reactive oxygen species (ROS) production. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 67 publications
3
16
0
Order By: Relevance
“…Theoretically, the stomatal properties are critical indicators to evaluate the plant response to stress environments [50]. In this study, we found that single drought or cold stress dramatically decreased the stomatal aperture (the ratio of width to length), which is consistent with the results in Zea mays L. [51]. Drought stress induced more direct and rapid injury on stomatal closure than cold stress, which was manifested as lower stomatal width in drought-treated E. nutans.…”
Section: Discussionsupporting
confidence: 87%
“…Theoretically, the stomatal properties are critical indicators to evaluate the plant response to stress environments [50]. In this study, we found that single drought or cold stress dramatically decreased the stomatal aperture (the ratio of width to length), which is consistent with the results in Zea mays L. [51]. Drought stress induced more direct and rapid injury on stomatal closure than cold stress, which was manifested as lower stomatal width in drought-treated E. nutans.…”
Section: Discussionsupporting
confidence: 87%
“…35−37 Among them, chlorophyll is the key substance that is used to absorb sunlight, and pores are an important channel for plant respiration and photosynthesis. 38,39 As shown in Figures 6 and 7C, the results revealed that the contents of Pn, Tr, WUE, Gs, chlorophyll a, chlorophyll b, total chlorophyll, and starch significantly decreased in the TMV treatment group at 1−5 dpi. The values of Pn, Tr, WUE, Gs, chlorophyll a, chlorophyll b, total chlorophyll, and starch increased by 135, 105, 20.0, 17.4, 40.9, 40.9, 41.9, and 117%, respectively, after treatment with compound T 8 at 5 dpi and were similar to those of the mock and NNM groups.…”
Section: Photosynthesis and Stomatal Parameters And Chlorophyll Contentmentioning
confidence: 80%
“…Organic matter accumulates by photosynthesis in plants, and leaves are the main organs of photosynthesis. Among them, chlorophyll is the key substance that is used to absorb sunlight, and pores are an important channel for plant respiration and photosynthesis. , …”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that MEL regulates the ascorbate-glutathione (AsA-GSH) cycle and proline metabolism while increasing the activity of antioxidant enzymes, which in turn protects the plant . Additionally, MEL ensures the proper functioning of the light system by reducing malondialdehyde (MDA) and electrolyte leakage while increasing chlorophyll concentration and accelerating nonphotochemical quenching . When exogenous MEL is applied, it stimulates the gene expression of Cu / Zn SOD , Fe / Zn SOD , and CAT , thereby improving plant performance and antioxidant activities under cold stress .…”
Section: Introductionmentioning
confidence: 99%
“…9 Additionally, MEL ensures the proper functioning of the light system by reducing malondialdehyde (MDA) and electrolyte leakage while increasing chlorophyll concentration and accelerating nonphotochemical quenching. 10 When exogenous MEL is applied, it stimulates the gene expression of Cu/Zn SOD, Fe/Zn SOD, and CAT, thereby improving plant performance and antioxidant activities under cold stress. 11 Furthermore, MEL upregulates the expression of cold signaling pathway genes such as C-repeat binding factor (CBF), thus enhancing plant cold tolerance.…”
Section: ■ Introductionmentioning
confidence: 99%